Analysis of Potential Assets of Brangus Cattle in Sragen Regency: Total Economic Value Approach - Ikhsan, Aulia Fauziah; Andarwati, Siti; Kusumastuti, Tri Anggraeni (Jurnal Ilmu-Ilmu Peternakan, 2024)
This research aims to analyze the Direct Use Value (DUV) of the population, production, and by-products, the Indirect Use Value (IUV) of employment and multiplier effects, the Option Value (OV) through the Willingness To Pay of farmers and influencing factors, as well as the Total Economic Value required to maintain the existence of Brangus cattle as a crossbreed in Sragen Regency. The research was conducted in Sragen Regency in January-February 2024 with the consideration that this is the largest population in Sragen Regency, Central Java of Brangus cattle. The respondents were determined by census as many as 170 respondents. Data collection was carried out through interviews using a questionnaire as a research instrument, 10 informants from slaughterhouses and cattle traders each were taken using the snowball sampling method based on the number of slaughterhouses and livestock markets in the area. Quantitative descriptive analysis by calculating DUV, IUV, OV, and the Contingent Valuation method is used to estimate the farmer's Willingness To Pay (WTP) in maintaining the existence of Brangus cattle. The DUV value is IDR11,316,615,446/year or in UT IDR1.11631E+11/year, IUV is IDR1.7900E+12/year or in UT IDR2.7254E+12/year and OV is IDR1,635,500,000/year or in UT IDR87,172,150,000/year. The largest TEV value is DUV which consists of a live cattle population of IDR2,991,000,681/year, total carcass and non-carcass of IDR6,755,207,690/year, sales of livestock manure IDR1,570,407,075/year. The TEV value of Brangus cattle in head units is IDR1.80294E+12/year or in UT IDR2.9242E+12/year. The DUV value on the production side shows the highest results because it is supported by the interest of breeders in maintaining livestock using a breeding system and this is an effort to continue raising Brangus cattle as a form of preserving cross-breed livestock because they have the potential for good meat yields. However, to increase the TEV value, it is necessary to add complete infrastructure, especially slaughterhouses, and utilize by-products through improving technology and strengthening institutions.